Optimizing Maize Yield With Hybrids Tolerant of High Plant Density in West and Central Africa - Wendm Ygzaw; Beatrice Elohor Ifie; Priscilla Francisco Ribeiro; Gloria Boakyewaa Adu; Eric Yirenkyi Danquah; Samuel Kwame Offei; Pangirayi Bernard Tongoona (Plant-Environment Interactions)
ABSTRACT The use of high plant density tolerant maize hybrids was one of the most successful interventions that boosted maize yield in the developed world. However, very little research has been conducted in the improvement of maize for high plant density tolerance in West and Central Africa (WCA). This study aimed to identify high plant density‐tolerant maize hybrids adapted to multiple environments. Forty‐eight maize hybrids were evaluated under three plant densities (low = 53,333, medium = 66,666, and high = 88, 888 plants ha−1). The experiment was conducted in four different environments in Ghana using 8 × 6 alpha lattice design with split plot arrangement. Plant density was the main plot and hybrids arranged in incomplete blocks within each plant density. The results revealed that the relative grain yield performance of the genotypes was dependent on plant density. Optimum plant density for the hybrids varied with growing environments. The highest grain yield of 9.5, 9.2, and 8.6 t ha−1 were obtained from the high plant density in Legon (minor season), Fumesua, and Legon (off‐season), respectively, and it was 26.7%, 22.7%, and 30% increase in comparison to the respective yield under the low density. F1 hybrids M131 × CML16, CML16 × TZEI1, CML16 × 87,036, TZEI387 × CML16, and ENT11 × 87,036 are good candidates for high‐density planting in high‐yielding environments. Grain yield performance of the maize hybrids was highest under high plant density for most of the growing environments. Thus, implementing high‐density planting for maize hybrids could be one of the options for increasing maize yield in West and Central Africa.